(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article is devoted to the problem of improvement of the constitutional guarantees of the property right. The author summarized the practice of the Constitutional Court of the Republic of Uzbekistan on the problems of protecting the right of property from arbitrary interference by third parties and the state.